Analysis of direct power control AC-DC converter under unbalance voltage supply for steady-state and dynamic response - Nor Azizah Mohd Yusoff; Azziddin M. Razali; Kasrul Abdul Karim; Raja Nor Firdaus Kashfi Raja Othman; Auzani Jidin; Nor Aishah Md Zuki; Nurfaezah Abdullah (International Journal of Electrical and Computer Engineering (IJECE), 2020)
This paper presents an analysis of Direct Power Control (DPC) technique for the Three-Phase Pulse Width Modulation (PWM) AC-DC converter under unbalanced supply condition. Unbalance condition will cause the presence of unbalanced current and voltages thus produce the negative components on the grid voltage as well as severe performance degradation of a grid connected Voltage Source Inverter (VSI). The input structures for conventional DPC has been modified with a three simpler sequence networks instead of coupled by a detailed Three-Phase system method. The imbalance voltage can be resolved by separating from the individual elements of voltage and current into symmetrical components called Sequence Network. Consequently, the input power relatively improved during unbalanced condition almost 70% through the measurement of Total Harmonic Distortion (THD) from the conventional Direct Power Control (DPC) in individual elements which is higher compared to separate components. Hence, several analyses are performed in order to analyze the steady state and dynamic performance of the converter, particularly during the load and DC voltage output reference variations.